Surface Stabilizing Speed-Tracking Control for PMSMs via Loop Adaptation and Order Reduction Approaches - Kim, Seok Kyoon; Lee, Kyo Beum (IEEE Journal of Emerging and Selected Topics in Power Electronics, 2023)
The proposed single-loop solution to the permanent-magnet synchronous motor (PMSM) speed-tracking problem provides improved transient performance and robustness by overcoming the two challenging points of parameter variation and performance inconsistency due to load changes. The features are summarized as follows: 1) the proportional-type control law exponentially stabilizes the desired surface with the disturbance observers (DOBs) through the order reduction property, resulting in the q-axis current independent single-loop structure for speed control with first-order speed error dynamics; 2) the parameter-independent angular acceleration observer renders the proportional-type surface-stabilizing control implementable without an additional sensor and direct time derivative operation based on the speed measurement; and 3) the adaptive convergence rate mechanism in the analytic form provides improved transient performance through the loop adaptation of the closed-loop system without requiring an additional optimization process. The experimental study demonstrates the practical advantages using a 1-kW PMSM drive system.
Keywords: Acceleration observers; Convergence; Disturbance observer; Order reduction; Permanent Magnet Synchronous Motor; Power-electronics; Robustness; Single loop; Surface stabilization; Vehicle's dynamics; Acceleration observer; disturbance observer (DOB); permanent-magnet synchronous motor (PMSM); speed control; surface stabilization